Teacher's Strategy in Improving Vocabulary Mastery: Integrating Humanistic Approach and Guthrie's Theory at MTsN 7 Kerinci: Strategi Guru dalam Meningkatkan Penguasaan Kosakata: Mengintegrasikan Pendekatan Humanistik dan Teori Guthrie di MTsN 7 Kerinci - Muhammad Agil Munawwar; Ahmad Jamin; Dhiraj Kumar (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2025)
This study aims to describe in depth the implementation of integrating humanistic approaches and Guthrie's theory to enhance mastery of Arabic vocabulary (mufradāt) and change student learning behaviors at MTsN 7 Kerinci. The research used a qualitative case study approach, with data collected through participatory observation across 12 meetings, in-depth interviews with three teachers and 15 students, and analysis of evaluation documents. Data were analyzed thematically using the Miles and Huberman model, with data condensation, data display, and findings verification. The results showed that the humanistic approach successfully created a favorable learning climate through building teacher-student emotional relationships. At the same time, the application of Guthrie's contextual repetition significantly improved vocabulary retention, from an average of 2-5 mufradāt per day to 10-15 mufradāt per day. The findings also revealed a transformation in student behavior, with students becoming more active and independent, and infrastructure limitations successfully overcome through teacher creativity in using simple media. The research implications indicate that integrating both approaches creates a holistic learning environment that supports the simultaneous development of cognitive and affective aspects. Keyword: Edwin Ray Guthrie, Humanistic Approach, Vocabulary (Mufradāt) Acquisation